DETERMINAN INITIAL RETURN PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING (IPO) DI BEI PERIODE 2016-2017 - Syazidha Qonisha Isnaini, (2020)
This research is a quantitative research that aims to find out the factors that influence the initial return. The factors that influence the determinant of the initial return used in this study are accounting information and non accounting information. Accounting information consist of profitability, financial leverage, liquidity, company size, earning per share, price earning ratio. Meanwhile, non accounting information is the reputation of underwriter. The sample used is the company conducting an Initial Public Offering (IPO) in 2016 and 2017. The sample selection does not use criteria because the companies that conduct an IPO every year are different and increasing, so the number of samples used are all IPO companies in the 2016 and 2017 period that listed on the Indonesia Stock Exchange (IDX). To test the hypothesis in this study using Multiple Linear Regression Analysis because the number of independent variables are more than two and using SPSS program with a significance level of 5%. The results of hypothesis testing concluded that the company size and earning per share variables have a negative and significance effect on initial return. While other variables, namely profitability, financial leverage, liquidity, price earning ratio, and underwriter reputation do not have a significant effect on initial return.